A Differential Probability Selection MAC Protocol Considering Energy Consumption in Wireless Sensor Networks. (18th April 2013) - Lee, Myungsub; Park, Chang-Hyeon
In the sensor network using distributed coordination function (DCF) of carrier sense multiple access/collision avoidance (CSMA/CA), sensor nodes have to necessarily compete with others for medium access and service, as the scale of network is increased. Under this situation, many nodes are to collide with each other, and hence this situation finally leads to overall increase of transmission delay which gives rise to the power consumption. This paper presents a differential probability selection MAC (DPSMAC) protocol which is efficient for medium access in the real-time sensor networks. The presented DPSMAC protocol is similar to the conventional CSMA/CA protocols, except that it does not use a time-varying contention window in which a node randomly selects a transmission slot. The DPSMAC adopts the fixed-size contention window with a nonuniform probability distribution in which each slot is selected by the differential probability distribution. The simulation using ns-2, a widely used network simulation package, gives that the proposed method can reduce the latency considerably as compared to the conventional IEEE 802.11 MAC protocols for a sensor network with up to 256 nodes. It also shows that the proposed scheme can realize the latency similar to that realized by the decentralized CSMA-based MAC protocol for real-time sensor networks that are sensitive to latency.